Integration of the ethnopedagogy of Jolotundo Temple's Ruwat Petirtaan tradition as the development of biology learning in the Merdeka curriculum - Rahmawati, Siti; Nugraha, Dewanta Arya; Abdurrahman, Ayi; Nurahman, Alfyn Abdan (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study identifies the values embedded in the local wisdom of the Jolotundo Temple’s Ruwat Petirtaan tradition and integrates them into biology learning within the Merdeka curriculum. A descriptive qualitative method was employed, using interviews and observations, and analyzed through triangulation and inductive approaches with an emphasis on meaning over generalization. Findings indicate that the tradition embodies gratitude for the abundance of water and natural resources across the preparation, implementation, and closing stages. It functions as a form of environmental conservation. This local wisdom can be integrated into Phase E Biology content, particularly biodiversity and conservation, ecosystems, and environmental change. The results serve as a reference for developing teaching materials, modules, student worksheets, project assignments, and assessment items, while also encouraging the incorporating of local wisdom into policies, conservation programs, and educational practices that are contextual, participatory, and sustainable. The implication is that cross-stakeholder commitment through school–community collaboration and continuous evaluation is required to ensure tangible impacts on learning, environmental stewardship, and the strengthening of cultural identity.